2019
DOI: 10.17113/ftb.57.01.19.5803
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Sensory Characteristics of Mould-Ripened Salami under Different Packaging Conditions

Abstract: The preservation of mould-ripened salami was investigated during 48 days at 19-20 °C under different packaging conditions: (i) high barrier film filled with air, 100 % N2 or under vacuum, (ii) biaxially oriented polypropylene film, (iii) microperforated polyethylene film and (iv) unpackaged. Sensory, texture profile, physicochemical and microbiological analyses were performed. Fungal quantification revealed two data groups. In group 1 (consisting of salami in microperforated polyethylene film, biaxially orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In the case of the mould salami, the largest decrease was found for aroma and taste at a level of 0.5 points. It was probably related to the excessive metabolic activity of the fungi during storage (excessive mould odour and odd odour) [ 38 ]. For all other sensory characteristics between samples, the differences were on the level of 0.2–0.3 points.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the mould salami, the largest decrease was found for aroma and taste at a level of 0.5 points. It was probably related to the excessive metabolic activity of the fungi during storage (excessive mould odour and odd odour) [ 38 ]. For all other sensory characteristics between samples, the differences were on the level of 0.2–0.3 points.…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum packaging keeps food in an anoxic or even anaerobic state, which can not only greatly inhibit the growth and reproduction of microorganisms but also reduce the food deterioration caused by the oxidation. When sausages and fish were vacuum-packaged, it was found that vacuum packing can more effectively control the growth and reproduction of microorganisms, prevent the loss of water, and maintain the original quality of food to a great extent than unpackaged food ( Amoli et al., 2019 ; Canel et al., 2019 ). Paraffin coating is commonly used method of food preservation as well, especially for the storage of fruits and vegetables, which can effectively prevent the loss of water and reduce the respiration to effectively alleviate the loss of nutrients.…”
Section: Introductionmentioning
confidence: 99%